INFLUENCE OF STEROIDAL AND NON-STEROIDAL CONTRACEPTIVE PILLS ON HORMONAL ALTERATIONS IN WISTAR FEMALE ALBINO RATS. - M.P.CHIKHALE, (International Journal of Pharma and Bio Sciences, 2015)
The effects of steroidal and non-steroidal contraceptive oral pills were studied in wistar female albino rats for 30 days. In steroidal pill fed rats FSH, estradiol and cortisol were found elevated at all the dose levels and LH, Progestesone and Testosterone were depleted significantly. In nonsteroidal contraceptive pill fed rats, no significant change was seen in FSH levels. However, there was a significant depletion in LH, Estradiol, Progesterone and Testosterone level. The steroidal and non-steroidal contraceptive oral pill in the present investigation indicates some negative effect on the ovarian activity.